Profile of College Students' Academic Self-Control - Riza Noviana Khoirunnisa; Damajanti Kusuma Dewi; Ira Darmawanti; Yohana Wuri Satwika (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study analyzes university students' academic self-control profiles in Surabaya City, Indonesia. Methods: The survey included the research method with a sample of 517 students. The data collection technique used a student response questionnaire. After that, quantitative descriptions were employed to assess the data and show the study outcomes. Results: The findings of the analysis demonstrate that students' academic self-control falls into the high range. Thus, students with good academic self-control will be able to control behavior consciously to choose goals, suppress urges, resist temptations, delay satisfaction, and control and regulate their emotions in academic goals. Novelty: The novel mapping of self-control focused on academics among university students makes this study innovative. Since academic procrastination is closely related to academic self-control, this mapping supports lecturers in reducing academic procrastination. Students can fully achieve academic and non-academic aims possible.